Status of the pelvic floor in young primiparous women. (28th July 2015) - Durnea, C. M.; O'Reilly, B. A.; Khashan, A. S.; Kenny, L. C.; Durnea, U. A.; Smyth, M. M.; Dietz, H. P.
ABSTRACT Objectives To investigate the postnatal prevalence of sonographically diagnosed pelvic floor trauma, and the correlations with various antenatal/intrapartum predictors in primiparous women. Methods This was a prospective cohort study performed in a tertiary hospital with 9000 deliveries per annum. Of those invited, 202 (23.2%) primiparous participants were assessed clinically at least 1 year after delivery by Pelvic Organ Prolapse Quantification (POP-Q), two/three‐dimensional transperineal sonography and quantification of serum collagen type III levels. Results There was a high prevalence of clinically significant pelvic organ prolapse (POP) on POP-Q staging: uterine prolapse, 63%; cystocele, 42%; and rectocele, 23%. Ballooning of the levator ani muscle (LAM) hiatus was detected in 33% and LAM avulsion in 29% of participants, with partial LAM avulsion occurring in 15% and complete avulsion in 14%. Postnatal POP symptoms (odds ratios (ORs) given here for presence of multiple prolapse symptoms) were positively associated with similar prepregnancy symptoms (OR, 7.2 (95% CI, 1.19–44.33)), LAM avulsion (OR, 4.8 (95% CI, 1.99–11.34)) and forceps delivery (borderline significance; OR, 1.8 (95% CI, 0.96–3.25)) and negatively associated with elective (OR, 0.2 (95% CI, 0.09–0.63)) and emergency (OR, 0.3 (95% CI, 0.12–0.83)) Cesarean section. LAM abnormality was associated with forceps delivery (OR, 4.9 (95% CI, 1.44–16.97)) and prolapse (OR, 6.8–11.7 (95% CI, 2.34–78.51)), whereas collagen levels did not play a role (OR, 1.001 (95% CI, 0.99–1.02)). Conclusions Clinically significant POP was common in relatively young premenopausal primiparous women. Partial or full levator avulsion was seen in 29% of participants and was associated with POP and related symptoms. Congenital factors seem to play little role in the etiology of LAM trauma, and the main risk factor seems to be forceps delivery. Avoidance of difficult vaginal deliveries may prevent severe pelvic floor trauma. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.